Перспективи інтродукції видів роду Hypericum L. - Makovetskaya, E.Y. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Comparative introductive research of 73 Hypericum L. species from all 30 sections of the genus, not growing in wild conditions in Ukraine, has been carried out in M.M. Grishko National Botanical Gardens (Kyiv, Ukraine). It is revealed that 18 species from 10 sections are perspective for industrial culture in Ukraine (Ascyreia Choisy, Androsaemum (Duhamel) Godron, Inodora Stef., Roscyna (Spach) R. Keller, Hypericum sectio typicum generis, Olympia (Spach) Nyman, Drosocarpium Spach, Oligostema (Boiss.) Stef., Crossophyllum Spach. and Adenosepalim Spach).